IMPROVING MARKETING RESEARCH IN PUBLIC TRANSPORT - Azamatovich, Berdiyorov Temur (International Journal of Psychosocial Rehabilitation, 2020)
Without the stable operation of the transport system and, first of all, without the accelerated development of the transport infrastructure, new efficient transportation technologies, it is difficult to ensure guaranteed accessibility of transport services for all consumers and reduce economic risks for carriers. Transport has a significant impact on the socio-economic development of every country. This article provides the population with actual recommendations on the content and methods of conducting transport services, certain types of marketing research, and the development of marketing research in the public transport system.